The Role of Cultural Identity in Spatial Dynamics: A Comparative Study of the Tengger and Bali Aga Traditional House - Basri, Syafine Charistalizaa Junaidi Hasan; Prajnawrdhi, Tri Anggraini; Wiryawan, I Wayan (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2025)
This study aims to analyze how cultural identity influences the spatial dynamics of traditional houses. In Indonesia, diverse local traditions are passed down through generations, shaping the identity of a region. These traditions affect the functions of living spaces, which evolve due to various factors, including social, economic, and environmental changes. If not addressed, this phenomenon could lead to the loss of cultural identity. The study focuses on the Tengger and Bali Aga tribes, using a qualitative comparative approach to analyze and compare their traditional spatial dynamics. The findings suggest that local customs, social activities, and the specific functions of these spaces significantly shape their transformation. The comparison reveals that while Tengger houses adapt to modern influences, Bali Aga houses adhere strongly to traditional spatial configurations. The study highlights the importance of preserving traditional elements and spatial configurations to maintain the cultural identity of these tribes. Furthermore, this study contributes to a deeper understanding of the relationship between spatial dynamics and cultural heritage.